Extraluminal migration of foreign body and its removal by lateral pharyngotomy and intraoperative C-arm - Sattien, Arun M.; Ali, Roshan; Lucy, Liano; Thingbaijam, Sudhiranjan (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2024)
Ingested foreign bodies are not unusual in Manipur. The most common of these are fish bones, which usually gets impacted in the tonsils, base of tongue or at the level of cricopharynx. Sometimes few may migrate extraluminally, or even extrude subcutaneously. We report a case of an ingested foreign body (beef bone) which had migrated to retropharyngeal space requiring lateral pharyngotomy using C-arm guidance for removal.